Aclidinium bromide combined with formoterol inhibits remodeling parameters in lung epithelial cells through cAMP. (December 2015) - Lambers, Christopher; Costa, Luigi; Ying, Qi; Zhong, Jun; Lardinois, Didier; Dekan, Gerhard; Schuller, Elisabeth; Roth, Michael
Graphical abstract: Graphic overview: Summary of the beneficial preventive effect of aclidinium bromide and formoterol on epithelial cell stability and ECM remodeling. Abstract: Combined muscarinic receptor antagonists and long acting β2 -agonists improve symptom control in chronic obstructive pulmonary disease (COPD) significantly. In clinical studies aclidinium bromide achieved better beneficial effects than other bronchodilators; however, the underlying molecular mechanisms are unknown. This study assessed the effect of aclidinium bromide combined with formoterol on COPD lung ( n  = 20) and non-COPD lung ( n  = 10) derived epithelial cells stimulated with TGF-β1  + carbachol on: (i) the generation of mesenchymal cells in relation to epithelial cells, (II) extracellular matrix (ECM) deposition, and (iii) the interaction of ECM on the generation of epithelial and mesenchymal cells. TGF-β1  + carbachol enhanced the generation of mesenchymal cells, which was significantly reduced by aclidinium bromide or formoterol. The effect of combined drugs was additive. Inhibition of p38 MAP kinase and Smad by specific inhibitors or aclidinium bromide reduced the generation of mesenchymal cells. In mesenchymal cells, TGF-β1  + carbachol induced the deposition of collagen-I and fibronectin which was prevented by both drugs dose-dependently. Formoterol alone reduced collagen-I deposition via cAMP, this however, was overruled by TGF-β1  + carbachol and rescued by aclidinium bromide. Inhibition of fibronectin was cAMP independent, but involved p38 MAP kinase and Smad. Seeding epithelial cells on ECM collagen-I and fibronectin induced mesenchymal cell generation, which was reduced by aclidinium bromide and formoterol. Our results suggest that the beneficial effect of aclidinium bromide and formoterol involves cAMP affecting both, the accumulation of mesenchymal cells and ECM remodeling, which may explain the beneficial effect of the drugs on lung function in COPD.